PENGARUH HARGA TERHADAP KEPUASAN PELANGGAN DI CAFE KOPI MASSA KOK TONG LIM MING TEBING TINGGI - Marpaung, Maria Veronika; Saputri, Marheni Eka (2021)
The growth of the culinary business in Tebing Tinggi City is growing as evidenced by the increasing number of cafes with various concepts. So that the level of competition is getting higher, one of which is the Kopi Massa Kok Tong Lim Ming Tebing Tinggi cafe. Problems occur, namely the decline in sales which is a reference for cafe owners to increase sales by improving the level of consumer satisfaction, one of the factors is pricing. This study aims to determine and analyze the effect of price on customer satisfaction. The research method used in this research is quantitative method with descriptive-causality research type. Sampling was done by non-probability sampling technique used is accidental sampling of the number of respondents 100 consumers from Café Kopi Massa Kok Tong Lim Ming located in Tebing Tinggi. The data analysis technique used is descriptive analysis and simple linear regression analysis. The results of the research based on descriptive analysis for the price variable are in a fairly good category, the customer satisfaction variable is in a good category and there is a positive and significant influence between price and customer satisfaction of 74.3% and the rest is influenced by other factors not examined.